A new species of Yunnanilus (Cypriniformes, Nemacheilidae) from Yunnan, southwest China - Zhi-Xian Qin; Wei-han Shao; Li-Na Du; Zhen-Xing Wang (Zoosystematics and Evolution, 2024)
A new species of Yunnanilus is described from the Nanpanjiang River, Yunnan, China. The new species, Yunnanilus polylepis, can be distinguished from other species of Yunnanilus by the following combination of characteristics: Processus dentiformis absent; eye diameter smaller than interorbital width; outer gill raker absent and 10 inner gill rakers on first gill arch; whole trunk covered by scales; nine branched dorsal-fin rays; 10 or 11 branched pectoral-fin rays; six branched pelvic-fin rays. Despite our phylogenetic analysis, which sheds light on the complex relationships among Yunnanilus species, the majority of Yunnanilus species are restricted to more localized environments and habitats. It is urgent to address the environmental threats that jeopardize their survival, especially given their generally restricted distribution.